Competitiveness and comparative advantages in agriculture (livestock approach) - Beres, Daniel; Mészáros, Kornélia (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2011)
This study compares the effect of Common Agricultural Policy implementation on comparative advantages of livestock production in four selected countries, namely Czech Republic, Hungary, Poland and Slovakia (V4). The comparative advantage of Czech Republic’s bovine production as well as Slovakian poultry production has improved. On the contrary, sheep production in Poland and Slovakia has lost its previous positive RSCA value, similarly to swine production in Czech Republic and horse production in Hungary. Furthermore, a detailed analysis of bovine production in V4 countries revealed that the formerly successful quality competition was replaced gradually by price competition during the examined period (1999-2010).